External audit quality and ownership structure: interaction and impact on earnings management of industrial and commercial Tunisian sectors - Kouaib, Amel (2014)
This article emphasizes the significance of researching the cross effect of using jointly external audit quality and ownership structure over managerial discretion in a largely unexplored, non-Western and emerging context. The analysis is based on a sample of 61 Tunisian firms listed and unlisted on the Tunis Stock Exchange and operating in the industrial and commercial sectors during the period 2007-2011. To provide evidence on this topic, we conduct an empirical examination. First, we examine the effect of external audit quality and ownership structure on the discretionary accruals for the whole sample. We find that only auditor reputation has a negative and significant effect on earnings management. Second, this article provides empirical evidence on the cross effect of external audit quality variables and capital concentration on earnings management. This test suggests that this combination has a negative and significant effect on earnings management in industrial firms but it has a positive and non significant effect in commercial firms. Finally, the third empirical test concerns the combined effect of external audit quality and institutional property on earnings management.We find thatthe cross effect ofthis combined relation is negatively and significantly associated with earnings management of industrial firms but it has no significant effect on the earnings management of commercial firms. As for the cross effect of the auditor seniority and the institutional property, it has a positive and a significant effect in the commercial sectors, while, it is positively and non-significantly associated with earnings management of industrial firms. DOI: http://dx.doi.org/10.1016/j.jefas.2014.10.001